2009
DOI: 10.1016/j.scitotenv.2009.03.008
|View full text |Cite
|
Sign up to set email alerts
|

The multi-annual carbon budget of a peat-covered catchment

Abstract: This study estimates the complete carbon budget of an 11.4 km 2 peat-covered catchment in Northern England. The budget considers both fluvial and gaseous carbon fluxes and includes estimates of particulate organic carbon (POC); dissolved organic carbon (DOC); excess dissolved CO 2 ; release of methane (CH 4 ); net ecosystem respiration of CO 2 ; and uptake of CO 2 by primary productivity. All components except CH 4 were measured directly in the catchment and annual carbon budgets were calculated for the catchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
107
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(120 citation statements)
references
References 65 publications
(69 reference statements)
10
107
0
Order By: Relevance
“…The baseline is a pre-erosion carbon balance of -20.3 gC m -2 yr -1 which derives directly from the Tallis (1994) sequestration data. This value is reasonable in the context of reported carbon sequestration values for northern peatlands (Gorham 1991), but is at the lower range of values reported by Worrall et al (2003Worrall et al ( , 2009 for blanket peatlands in the northern Pennines, and is at the lower end of measured UK values reported in Billett et al (2010, this Special). This is consistent with the southerly position and relative dryness of the southern Pennines; however, it should be noted that the values are also lower than measured data at an intact Bleaklow site (Billett et al this Special).…”
Section: Bleaklow Carbon Budgetssupporting
confidence: 85%
“…The baseline is a pre-erosion carbon balance of -20.3 gC m -2 yr -1 which derives directly from the Tallis (1994) sequestration data. This value is reasonable in the context of reported carbon sequestration values for northern peatlands (Gorham 1991), but is at the lower range of values reported by Worrall et al (2003Worrall et al ( , 2009 for blanket peatlands in the northern Pennines, and is at the lower end of measured UK values reported in Billett et al (2010, this Special). This is consistent with the southerly position and relative dryness of the southern Pennines; however, it should be noted that the values are also lower than measured data at an intact Bleaklow site (Billett et al this Special).…”
Section: Bleaklow Carbon Budgetssupporting
confidence: 85%
“…The overall C balance of the largest catchment at Moor House (Trout Beck; 11.4 km 2 ) has been the focus of a recent paper by Worrall et al (2009). Using both direct measurements (e.g.…”
Section: Budgets and Fluxes At Moor House (N England)mentioning
confidence: 99%
“…The method used for estimating excess dissolved CO 2 in runoff from fresh soil water samples drawn from piezometers in described in Worrall et al (2009). POC fluxes losses (surface lowering) are measured from annual measurements of nests of erosion pins (12 pins per plot).…”
Section: Fluxes On Bleaklow (N England)mentioning
confidence: 99%
See 1 more Smart Citation
“…Such additional rainfall may also drive increased fluxes of fluvial carbon from the peatlands in the uplands. It has been suggested that discharge is the major control of dissolved organic carbon fluxes from peatlands, which could explain a large proportion of recent increased flux estimates (Worrall et al 2003(Worrall et al , 2009. Similarly, it is likely that discharge acts as a crucial control on particulate carbon fluxes from upland peatlands, particularly in winter when peat may be more susceptible to loosening by freeze-thaw (Holden et al 2007a) and given that there are large areas of bare peat and open ditches with available sediment for mobilisation (Holden 2005, Holden et al 2006.…”
Section: Changes In Rainfall Gradients 1961-2000mentioning
confidence: 99%